Retirement delay unified or differentiated: Based on the interaction between pension deficit and labor market - Zou Tieding; Ye Hang (China Finance and Economic Review, 2016)
Background: The pension deficit has been rapidly enlarging for more than a decade. If the retirement age is set at a low level, it might trigger a pensions crisis. Since the average life span of the Chinese has extended from 71 to 76 years old in last ten years, the feasibility of rising the retirement age has also been promoted. Methods: This paper aims to construct a mathematical model for choosing a proper policy about raising retirement age on the basis of the interaction between shortage of pension funds and labor market. It has also conducted a simulation analysis over the economic efficiency and political feasibility of a uniformed or a differentiated retirement-age delay policy. Results: Our findings show that it is up to how effective the pension deficit is closed, how many employments will be crowded out, and whether it is politically acceptable that the length and kind of the delay is decided. From the policy effect of raising retirement age, a soft approach to delaying retirement will be better than a tough one, and a differentiated method will be better than a uniformed one. The root cause for the inconsistency of the policy effect is the discrepancies in terms of wage rate and job fulfillment, brought by different human capital situations and individual differences of the insured. The shortage of pension funds can be more effectively closed, and the impact on new labor force will be reduced, if we employ a differentiated approach to delay retirement according to the pattern of human capital accumulation and the supply and demand status of labor force. Conclusions: Based on the above research, Not only can the differentiated approach crowd out fewer new employees, but also it can acquire support from the majority of the insured. We must attach importance to the role of human capital investment in addressing pension and employment crises, especially the low- skilled labor, can get more vocational training and academic education.
Keywords: 330; Pensions; Shortage of pension funds; The retirement delay; Labor market